2020
DOI: 10.1021/acsabm.9b00983
|View full text |Cite
|
Sign up to set email alerts
|

Poly(l-lactic acid) (PLLA)/MgSO4·7H2O Composite Coating on Magnesium Substrates for Corrosion Protection and Cytocompatibility Promotion

Abstract: Magnesium (Mg) and its alloys show excellent potential as orthopedic implantable materials, with their in vivo degraded Mg ions (Mg 2+ ) known to promote the growth of new bone. However, the swift corrosion process during implantation has greatly hindered its clinical applications. A method to counter the high rate of corrosion is to coat Mg substrates on surfaces with a thin layer of biodegradable polymer. Although such a coating reduces the long-term corrosion rate, it also prevents the shortterm release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…To restore the bone functions, the various biodegradable implant materials such as bioglass, hydroxyapatite, and so forth are utilized as prosthesis. Among them, magnesium was suggested as one of the suitable materials for bone augmentation and distraction osteotomy as it possesses better mechanical properties than polymers and superior biocompatibility than titanium. , Magnesium is vital for bones and dental health. The absence of Mg in the enamel on the teeth leads to dissolution in the acidic condition .…”
Section: Introductionmentioning
confidence: 99%
“…To restore the bone functions, the various biodegradable implant materials such as bioglass, hydroxyapatite, and so forth are utilized as prosthesis. Among them, magnesium was suggested as one of the suitable materials for bone augmentation and distraction osteotomy as it possesses better mechanical properties than polymers and superior biocompatibility than titanium. , Magnesium is vital for bones and dental health. The absence of Mg in the enamel on the teeth leads to dissolution in the acidic condition .…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid coating with suitable amount of GO‐AgNPs simultaneously showed favorable biocompatibility, indicating its practical value in orthopedic implantation. Considering the great suppression of the initial release of Mg 2+ , which plays a vital role in the new bone formation, after the implementation of a anticorrosive barrier layer on Mg substrates will retard the bone fracture healing process, some researchers tried to add some Mg‐based compounds into the surface coating to increase the concentration level of Mg 2+ within the surrounding environment by the diffusion and dissolution of such loaded reagents 96,97 . We have proposed a PLLA/MgSO 4 ⋅7H 2 O composite coating system to solve the referred problem 96 .…”
Section: Polymeric Coatings On Mg‐based Biomaterialsmentioning
confidence: 99%
“…Considering the great suppression of the initial release of Mg 2+ , which plays a vital role in the new bone formation, after the implementation of a anticorrosive barrier layer on Mg substrates will retard the bone fracture healing process, some researchers tried to add some Mg‐based compounds into the surface coating to increase the concentration level of Mg 2+ within the surrounding environment by the diffusion and dissolution of such loaded reagents 96,97 . We have proposed a PLLA/MgSO 4 ⋅7H 2 O composite coating system to solve the referred problem 96 . The embedded water‐soluble MgSO 4 ⋅7H 2 O particles can easily diffuse out and dissociate to generate Mg 2+ when contact with aqueous solution, so the quick release of Mg 2+ at early stage was achieved without deteriorating the corrosion resistance.…”
Section: Polymeric Coatings On Mg‐based Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alaei et al [95] also revealed that CS-BG nanocomposite coatings had great adhesion to the Mg substrate and the ability to form apatite after 7 days in SBF. Zhu et al [113] showed that PLLA/magnesium sulfate heptahydrate (MgSO 4 •7H 2 O) composite-coated samples could enhance cell adhesion and proliferation and act as a productive barrier on the surface of pure Mg substrate. Jin et al [111] prepared a composite coating consisting of FHA and PLA that was fabricated on MAO-Mg alloy.…”
Section: Composite Polymer Coatingsmentioning
confidence: 99%